Analysis of Tribological Researches of Gear Cutting Processes of Cylindrical Gears in Real and Model Conditions - Sovilj, Bogdan; Sovilj-Nikic, Sandra; Sovilj-Nikic, Ivan (Current Approaches in Science and Technology Research Vol. 7, 2021)
The availability, adaptability, reliability and productivity of modern industrial complexes, maintenance costs, energy costs and industrial production costs depend also on the intensity of wear of the elements of tribo-mechanical systems. Gear cutting operations are usually a bottleneck of production, especially in higher types of production. The complexity of the procedure of determining tribological properties of tribo-mechanical system elements from an economic aspect is provoked by the presence of possibility to choose numerous parameters for monitoring the process development of their wear as well as selection of wear criteria.